Corrosion Product Structures of Steel Samples Exposed to Amine Solutions Used for H2s Removal. (18th September 2015) - Alpuche-Aviles, Mario A; Waite, Scott; Malkiewich, Ryan; Parajuli, Suman; Muñoz, Maria; Chhetri, Pushpa
Abstract : We present the corrosion effects of heat stable salts (HSS), i.e., amine salts and amino acids that occur during removal of H2 S from petroleum and natural gas with methyl diethanolamine (MDEA) solutions. The salts include heat stable salts and amine degradation products. Corrosion rates were measured using coupon weight loss in liquid and vapor phases in stirred solutions that model amine plant environment (e.g., refinery systems) in a chamber that enables exposure of samples to the gas and liquid phases. At increasing concentration of HSS the corrosion products show well-defined structures in the nanometer scale for the samples exposed to the liquid phase. However, this was not observed in the vapor phase. The corrosion products include amorphous, columnar and disk-shaped structures depending on exposure conditions. We propose that the substrates become initially passivated and that localized corrosion takes place under the conditions of our study that mimic the HSS build-up.